A measurement of the τ lifetime - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Bock, B; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; et al. (Springer-Verlag, 1988)
We have reconstructed 695 three-track τ decay vertices using a high resolution drift chamber close to the interaction point. From the distribution of decay lengths we measure the lifetime to be (3.06 ±0.20±0.14)×10-13 s. Using this result we find that the ratio of charged weak coupling constant for the τ to that of the μ, Gτ/Gμ=0.967±0.040 consistent with the concept of lepton universality. © 1988 Springer-Verlag.